A new genus of cave spider from Neotropical region (Gnaphosidae: Prodidominae) - Rodrigues, Bruno V. B.; Cizauskas, Igor; Lemos, Yuji (Zootaxa, 2020)
A new monotypic genus of Prodidominae, Indiani gen. nov., is proposed to include one cave species collected in limestone caves from Minas Gerais, Brazil: Indiani gaspar sp. nov. (♂♀). Based on a recent phylogenetic analysis of Prodidominae, the new genus is closely to other Neotropical Prodidominae, such as Lygromma, Brasilomma and Moreno by sharing a classic claw tuft clasper. Indiani gen. nov. is characterized by a ventral parallel rows of strong spines on tibia and metatarsus I–II, male palp with sclerotized conductor and the robust median apophysis is curved retrolaterally; the female epigyne has an anterior atrium and a posterior extension of the epigynal plate. As other cave Prodidominae, Indiani gen. nov. has morphological characteristics, such as loss or reduction of eyes and weak pigmentation, that indicate an adaptation for living in subterranean environments.